2020
DOI: 10.1186/s12889-020-09129-y
|View full text |Cite
|
Sign up to set email alerts
|

Anemia prevalence, severity and associated factors among children aged 6–71 months in rural Hunan Province, China: a community-based cross-sectional study

Abstract: Background In recent 10 years, with the rapid socioeconomic development and the extensive implementation of children nutrition improvement projects, the previous epidemiological data cannot reflect the actual level of anemia among children in China, especially in rural areas. Therefore, this study analyzed the prevalence, severity and associated factors of anemia among children aged 6–71 months in rural Hunan Province. Methods A comm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
0
23
2
1
Order By: Relevance
“…In this study, the prevalence of anemia among children aged 6-59 months in Ethiopia was 57.56% (95%CI: 56.50%, 58.61%) ranged from 42.66% in the Amhara region to 83.24% in the Somali region. This was higher than a study reported in Ghana [41] and China [42]. Even though the combined strategies particularly iron supplementation and infectious disease management (such as malaria and helminths infections) are being introduced by the WHO to combat anemia, anemia remains a serious health care problem in Ethiopia.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, the prevalence of anemia among children aged 6-59 months in Ethiopia was 57.56% (95%CI: 56.50%, 58.61%) ranged from 42.66% in the Amhara region to 83.24% in the Somali region. This was higher than a study reported in Ghana [41] and China [42]. Even though the combined strategies particularly iron supplementation and infectious disease management (such as malaria and helminths infections) are being introduced by the WHO to combat anemia, anemia remains a serious health care problem in Ethiopia.…”
Section: Discussionmentioning
confidence: 67%
“…In women, loss of iron from the body mostly happens through sloughing of duodenal enterocytes and through menstrual and postpartum blood loss that deprive the circulatory pool of iron that is available for its utilization in target organs resulting in the state of functional iron deficiency, which is measured in the form of hemoglobin (iron is the main ingredient of hemoglobin) [33]. Low red blood cell indices are considered sensitive indicators of decreased iron availability for hematopoietic tissues [34]. A decrease in Hb, MCV, and MCH reflects iron-restricted erythropoiesis in the bone marrow, which reflects a typical IDA presentation [31].…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…However, the present study found that iron-deficiency anemia accounted for only 27.33% of anemia in this area. The lower proportion of iron-deficiency anemia may be related to the implementation of a government strategy for its prevention and treatment [26,27]. Nutritional supplementation can effectively reduce the risk of anemia in children [28][29][30].…”
Section: Association Of Anemia and Neurobehavioral Development Of Children Aged 6-24 Monthsmentioning
confidence: 99%